PENGARUH MODEL EXPERIENTIAL LEARNING BERBANTUAN MEDIA PEMBELAJARAN YOUTUBE TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 3 BALIKPAPAN - Fitri, Andi; Sudarman, Sudarman; Abu, Ilham (Faculty of Teacher Training and Education, Mulawarman University, 2023)
This research aims to determine the effect of the experiential learning model assisted by YouTube learning media on the learning outcomes of class X students at SMA Negeri 3 Balikpapan. This research uses a quasi-experimental method with a nonequivalent control group design. The subjects of this research were students in class X-3, totaling 36 students, as the experimental class and X-6, totaling 36 students, as the control class. The data collection technique used in this research is a test, namely pretest and posttest, then supported by other data in the form of documentation with data analysis using the sample t-test. The research results show that the sig. (2-tailed) t-test for Equality of means is 0.001 so that the significance value is 0.001 < 0.05, which means H0 is rejected and Ha is accepted. So, it can be concluded that there is a significant influence of the experiential learning learning model assisted by YouTube learning media on the economic learning outcomes of class X SMA Negeri 3 Balikpapan students.